Perancangan Sistem Pakar Mendiagnosa Anemia Menggunakan Metode Fuzzy Mamdani - Supriadi, Yusuf; Suhendi, Hendi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Anemia is a condition of reduced red blood cells in the body lower than the normal amount, or what is commonly referred to as erythrocytes in the blood circulation or hemoglobin so that it is unable to fulfill its function as an oxygen carrier to all body tissues. An expert system is a system designed to mimic the experience of an expert in answering questions and solving problems. By using an expert system, a non-expert can solve problems and make decisions that would normally be made by an expert. Expert systems are now being developed in various fields, expert systems in the health sector are widely developed to detect various diseases with various methods. The fuzzy mamdani method is a method that is also often known as the MAX-MIN or MAX-PRODUCT method. The fuzzy mamdani method can help users in terms of detecting diseases based on symptoms that arise and lifestyle and provide diagnostic results for further action. Based on the description above, it can be seen that the fuzzy method is one method that has been widely used in software development for the diagnosis of a disease. Modeling this expert system to determine anemia based on the symptoms felt by patients.